Zooplankton indices in the evaluation of the ecological state of the eutrophic lake (Case study: Karasikha Lake, Russia) - Оlga Iurievna Derevenskaia (University of Guilan, 2021)
Long-term (1998-2018) studies have been carried out on the small lake, Karasikha, located in the territory of the Volga-Kama State Nature Biosphere Reserve. Physicochemical characteristics of the lake water classify it as eutrophic, polluted, with a low oxygen content, but a high content of organic matter and phosphates. In parallel, some studies were carried out on its zooplankton community. Karasikha Lake is the habitat of 70 species of planktonic rotifers and crustaceans identified. Based on the number of species, rotifers predominated and their largest number belonged to Brachionidae family. On average 3-4 species were dominant, as indicators of eutrophic and polluted waters. However, with a relatively high species richness of zooplankton, the community has low quantitative indicators. The low oxygen content in the water column makes zooplankton concentrate mainly in the epilimnion layer (up to 2-3 m in depth). The lowest quantitative indicators of zooplankton are characteristic of the under-ice period, which is also associated with a lack of oxygen in the water. The community is dominated by indicators of dirty waters. The structure of zooplankton communities is typical of highly polluted lakes. Indices based on the taxonomic structure of zooplankton classify the reservoir as highly eutrophic and even hypertrophic.